Oral Ecchymosis in elderly: Senile purpura - Srikanth H Srivathsa (Wolters Kluwer Medknow Publications, 2015)
Senile purpura is the clinical condition where purpuric spots and ecchymosis develop at the site of minimal injury. It occurs due to laxity of the connective tissue. Oral manifestation of this disease is rare and when one encounters such a case, proper examination with extensive differential diagnosis should be considered along with appropriate investigations. A case of senile purpura in an elderly patient who had developed oral ecchymosis secondary to denture injury is being reported.